Analisis Tingkat Berpikir Kreatif Mahasiswa dalam Memecahkan Soal Matematika Ditinjau Dari Keaktifan Kelas Daring - Tri Budi; Nur Izzati (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
The heterogeneity of mathematics education students is a challenge for lecturers and students at the same level who want to research because of the many characteristics. Creativity is not only intended for people with high mathematical abilities but also for everyone. The study was conducted online due to the COVID-19 outbreak. This research is a descriptive qualitative research that aims to describe the level of creative thinking of students in solving math problems online and to describe the activity of online classes. The research subjects studied were students of the 6th semester 6th semester mathematics education research methodology (metopen) at Raja Ali Haji Maritime University, totaling 23 people. The data analysis technique in this study uses the methods proposed by Miles and Huberman, namely data reduction, data presentation and verification or conclusions. Data collection is done by providing problem solving questions to all subjects online. The results of the study on the average creative thinking level of the 23 people were quite creative and active.